Localization and Characterization of Flavivirus Envelope Glycoprotein Cross-Reactive Epitopes - Crill, Wayne D. (American Society for Microbiology, 2004)
The flavivirus E glycoprotein, the primary antigen that induces protective immunity, is essential for membrane fusion and mediates binding to cellular receptors. Human flavivirus infections stimulate virus species-specific as well as flavivirus cross-reactive immune responses. Flavivirus cross-reactive antibodies in human sera create a serious problem for serodiagnosis, especially for secondary flavivirus infections, due to the difficulty of differentiating primary from secondary cross-reactive serum antibodies. The presence of subneutralizing levels of flavivirus cross-reactive serum antibodies may result in a dramatic increase in the severity of secondary flavivirus infections via antibody-dependent enhancement. An understanding of flavivirus E-glycoprotein cross-reactive epitopes is therefore critical for improving public health responses to these serious diseases. We identified six E-glycoprotein residues that are incorporated into three distinct flavivirus cross-reactive epitopes. Two of these epitopes which are recognized by distinct monoclonal antibodies contain overlapping continuous residues located within the highly conserved fusion peptide. The third epitope consists of discontinuous residues that are structurally related to the strictly conserved tryptophan at dengue virus serotype 2 E-glycoprotein position 231.